CRGDyK modified pH responsive nanoparticles for specific intracellular delivery of doxorubicin. (15th January 2016) - Qiu, Lipeng; Hu, Qing; Cheng, Liang; Li, Ling; Tian, Chenmin; Chen, Wei; Chen, Qing; Hu, Wen; Xu, Lu; Yang, Jia; Cheng, Lifang; Chen, Dawei
Graphical abstract: Abstract: Stimuli-responsive nanocarriers attract wide attention because of the unique differences in microenvironment between solid tumors and normal tissues. Herein, we reported a novel cRGDyK peptide modified pH-sensitive nanoparticle system based on poly(ethylene glycol)-poly(2, 4, 6-trimethoxy benzylidene-pentaerythritol carbonate) (PEG-PTMBPEC) diblock copolymer, which was expected to destroy tumor angiogenesis and kill tumor cells simultaneously. Doxorubicin (DOX)-loaded nanoparticles (NPs) were characterized to have a uniform size distribution, high entrapment efficiency, good stability in plasma as well as a pH dependent drug release pattern. Blank NPs were non-toxic to both tumor cells and normal cells, while DOX-loaded cRGDyK peptide modified NPs (cRGDyK-NPs) exhibited the pronounced cytotoxicity against B16 cells and human umbilical vein endothelial cells (HUVEC) overexpressing αv β3 integrin receptors. Cellular uptake studies revealed that the highly efficient uptake of cRGDyK-NPs was attributed to the receptor-mediated endocytosis and acidic-triggered drug release. Importantly, cRGDyK-NPs could dramatically reduce the systemic toxicity of DOX and exert excellent tumor killing activity in vivo . The cRGDyK modified pH-sensitive nanocarrier is a promising vehicle for intracellular drug delivery to αv β3 integrin receptor overexpressed tumor cells and neovascular cells. Statement of Significance: Slow intracellular drug release and poor tumor targeting capacity are still the critical barriers of polymeric nanoparticles (NPs) for the treatment efficiency of chemotherapy. In the present study, we designed cRGDyK peptide modified poly(ethylene glycol)-poly(2, 4, 6-trimethoxybenzylidene-pentaerythritol carbonate) (cRGDyK-PEG-PTMBPEC) NPs with active targeting and fast pH-triggered drug release. Doxorubicin (DOX)-loaded cRGDyK-PEG-PTMBPEC NPs exhibited pronounced cytotoxicity and enhanced cellular uptake against B16 cells and human umbilical vein endothelial cells overexpressing αvβ3 integrin receptors. Moreover, the active targeted pH-sensitive NPs can enhance the antitumor activity and reduce the systematic toxicity of DOX in vivo .